Heterogeneity of the Peripheral Circadian Systems in Drosophila melanogaster: A Review - Ito, Chihiro; Tomioka, Kenji (Frontiers in Physiology, 2016)
Circadian rhythms in organisms are involved in many aspects of metabolism, physiology, and behavior. In many animals, these rhythms are produced by the circadian system consisting of a central clock located in the brain and peripheral clocks in various peripheral tissues. The oscillatory machinery and entrainment mechanism of peripheral clocks vary between different tissues and organs. The relationship between the central and peripheral clocks is also tissue-dependent. Here we review the heterogeneous nature of peripheral circadian clocks in the fruit fly Drosophila melanogaster and their dependence on the central clock, and discuss their significance in the temporal organization of physiology in peripheral tissues/organs.